COMMENSAL MICROORGANISMS IN DEVELOPMENT OF THE CHILDREN IMMUNE SYSTEM AND NEW FACILITIES OF PROBIOTICS USAGE - S. V. Il'ina (Вопросы современной педиатрии)
Numerous and various microorganisms inhabit human skin and mucous membranes. One of the functions of the microbiota is modulation of the immune system, and microorganisms begin to participate in development of children immune system at the prenatal state. Initial colonization which takes place during post-natal period depends on many factors, type of nutrition being the most important of them. The other factors associated with the modern mode of life are considered to influence the process of organism microflora formation. A number of articles considering «hygienic theory» which relate the increase of allergic and autoimmune disorderswith lower level of contact of the macroorganism with microorganisms in childhood have been published in this field. Thus, usage of probiotics in order to modulate the immune system and decrease the negative effects of various factors depressing the microflora of the organism of interfering its formation is of a great scientific and practical interest. Due to this fact the most prospective for children is usage of Bifidobacterium which predominate in stool of breas-fed infants and have the highest level of safety. A number of scientific studies demonstrate the established efficacy of probiotics in prophylaxis of acute respiratory tract infections and treatment of allergic disorders in children. The represented review contains analysis of scientific articles covering issues of microflora role in formation of children immune system and possibilities of probiotics usage in immunocorrection.